2018
DOI: 10.1177/0300060518761303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of infectious ulceration over tophi in patients with gout

Abstract: ObjectiveThe aim of this study was to investigate the clinical characteristics of infectious ulceration over tophi in patients with gout.MethodsParticipants were recruited from the First Affiliated Hospital of Wenzhou Medical University. The clinical characteristics of the patients and wound characteristics were recorded.ResultsOf the 38 enrolled patients, 18 were found to have infectious ulceration over tophi. Staphylococcus aureus was the most common pathogen and was identified in nine patients. Patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Gout is a rheumatic disease resulting from deposition of monosodium urate crystal within joints due to long-lasting hyperuricaemia (Richette & Bardin, 2010). Due to prolonged and uncontrolled hyperuricaemia, tophi, a form of monosodium urate crystal, deposits in joints, tendon sheaths, soft tissues and bony prominences, causing negative effects on musculoskeletal function (Rider & Jordan, 2010;Xu, Zhu, & Zhang, 2018). The finding from this current research is similar to findings of past studies by Spaetgens et al (2017), in which gout was found to be associated with pneumonia and urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…Gout is a rheumatic disease resulting from deposition of monosodium urate crystal within joints due to long-lasting hyperuricaemia (Richette & Bardin, 2010). Due to prolonged and uncontrolled hyperuricaemia, tophi, a form of monosodium urate crystal, deposits in joints, tendon sheaths, soft tissues and bony prominences, causing negative effects on musculoskeletal function (Rider & Jordan, 2010;Xu, Zhu, & Zhang, 2018). The finding from this current research is similar to findings of past studies by Spaetgens et al (2017), in which gout was found to be associated with pneumonia and urinary tract infection.…”
Section: Discussionmentioning
confidence: 99%
“…Polyarticular arthritis is more common with chronic tophaceous gout [ 7 ]. Chronic tophaceous gout develops in approximately 10 years in untreated patients, and 12–35% develops tophi [ 8 , 9 ]. Diagnosis is usually clinical, but synovial fluid analysis for monosodium urate crystal is gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…The trauma history may provide a hint to possible causative microorganisms (Table 1). A gout tophus that is infected and perforates into the joint [26], or adjacent severe skin and softtissue infection [27,28], are less frequently reported routes of exogenous infections.…”
Section: Septic Arthritismentioning
confidence: 99%